GHACHAR GHOCHAR: THE SILENT STRUGGLES OF PRIVILEGED YOUTH - K.N, Nijamol K.N (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This essay explores Vivek Shanbhag’s novel Ghachar Ghochar as a nuanced depiction of the silent struggles faced by privileged youth in post-liberalisation India. Departing from the traditional archetype of the ‘angry old man’ often seen in post-colonial literature, the novel’s narrator is a passive, introspective character who navigates a materially comfortable but emotionally hollow life. The essay contrasts this character with figures like Balram Halwai from Aravind Adiga’s The White Tiger, illustrating opposing relationships with wealth and social mobility. The narrator’s familial and marital tensions underscore his lack of agency, as he remains entangled in generational wealth and societal expectations. Through the metaphor of the narrator’s emotional inertia, the novel critiques a cultural shift where ambition is replaced by complacency and introspection by inaction. Ultimately, Ghachar Ghochar serves as a reflection on the evolving culture of India’s middle class, highlighting the psychological burden of privilege and the loss of existential purpose in a rapidly changing socio-economic landscape.